Factor this polynomial: x^2 + 6x + 9 (x+3)(x+3) (x-3) (x-3) (x-3) (x+3) (x+3) (x-3)

Question

Factor this polynomial: x^2 + 6x + 9
(x+3)(x+3)
(x-3) (x-3)
(x-3) (x+3)
(x+3) (x-3)

in progress 0
Cora 2 hours 2021-10-14T11:31:20+00:00 2 Answers 0

Answers ( )

    0
    2021-10-14T11:32:42+00:00

    Answer:

    (x+3)(x+3)

    Step-by-step explanation:

    1) this polynomial is in the form of ax^2+bx+c

    c=9

    b=6

    a=1

    what*what=c(9)

    and what+what=b(6)

    3 is the answer to both questions:

    now substitute “3x” in place of “6”

    x^2+3x+3x+9

    split in 2 groups:

    group a) (x^2+3x)

    gcf of group a=x

    x(x+3)

    group b) (3x+9)

    gcf of group b=3

    3(x+3)

    combine the numbers OUTSIDE the parantheses

    so

    (x+3)(x+3)

  1. Emma
    0
    2021-10-14T11:33:11+00:00

    Answer:

    (x+3)(x+3)

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )